Sensibilidade de Hemileia vastatrix à fungicidas triazóis - Gilioli, Fernando (2023)
The Rust (Hemileia vastatrix) is the main coffee disease, as it can cause significant losses of more than 50% in production. In recent years, this disease has worried not only coffee growers, but also researchers and consultants, when reporting the inefficiency of systemic fungicides or their loss of control, and also the high incidence in resistant cultivars. This control inefficiency leads to its report at high intensities at harvest time, from June to August, described as “late rust”, often attributed to rains at the beginning of winter and climate changes. In other crops, fungal resistance to these fungicides has already been identified. However, the question remains, could it be resistance to fungicides? Given this scenario, the objective of this work was to evaluate the sensitivity of Hemileia vastatrix, both in vitro and in vivo, to the main triazol fungicides (DMI's) currently used by coffee farmers in Brazil. For this, in vitro, greenhouse and field experiments were carried out. The in vitro experiment was carried out in microplates, with 8 isolates of H. vastatrix and 7 different doses of fungicides with epoxiconazole, cyproconazole, flutriafol, copper hydroxide and mancozeb, in order to identify the lethal dose to inhibit 50% of uredospores germination (Ec50). In vitro, the results showed sensitivity of populations of Hemileia vastatrix to the active principles tested, however, there was variation in the sensitivity level among the isolates, with flutriafol treatment having the highest Ec50. In this case, the ideal dose response for in vitro sensitivity tests was between 32 and 128mg/Kg of active ingredient for triazoles and multisite fungicides, 2mg/Kg for mancozeb and 8mg/Kg for copper hydroxide. In the experiments in the greenhouse and in the field, the dose of fungicides registered for the control of rust was used and the incidence and severity of the disease were evaluated. Data were integrated into the area under the disease progress curve (AUDPC) and were compared using the F test of the analysis of variance. In a greenhouse, no difference was observed between the isolates and the fungicides. In the field, differences in AUDPC were observed between systemic and site-specific fungicides (DMI's) and protectors or multisites and between years in relation to productivity. In the field, the control treatments, mancozeb and copper hydroxide showed a higher incidence of rust. All triazoles were efficient in controlling rust in the field, however, they showed differences in relation to AUDPC and control efficacy. Due to this evidence, it is necessary to study at molecular level the existence of resistance to this group of fungicides.